Critical Evaluation of the Lund Concept for Treatment of Severe Traumatic Head Injury, 25 Years after Its Introduction - Grände, Per-Olof (Frontiers in Neurology, 2017)
When introduced in 1992, the Lund concept (LC) was the first complete guideline for treatment of severe traumatic brain injury. It was a theoretical approach, based mainly on general physiological principles—i.e. of brain volume control and optimization of brain perfusion and oxygenation of the penumbra zone. The concept gave relatively strict outlines for cerebral perfusion pressure (CPP), fluid therapy, ventilation, sedation, nutrition, the use of vasopressors, and osmotherapy. The LC strives for treatment of the pathophysiological mechanisms behind symptoms rather than just treating the symptoms. The treatment is standardized, with less need for individualization. Alternative guidelines published a few years later (e.g. the Brain Trauma Foundation guidelines and European guidelines) were mainly based on meta-analytic approaches from clinical outcome studies and to some extent from systematic reviews. When introduced, they differed extensively from the LC. We still lack any large randomized outcome study comparing the whole concept of BTF guidelines with other guidelines including the LC. From that point of view, there is limited clinical evidence favoring any of the s-TBI guidelines used today. In principle, the LC has not been changed since its introduction. Some components of the alternative guidelines have approached those in the LC. In this review, I discuss some important principles of brain hemodynamics that have been lodestars during formulation of the LC. Aspects of ventilation, nutrition, and temperature control are also discussed. I critically evaluate the most important components of the LC 25 years after its introduction, based on hemodynamic principles and on the results of own an others experimental and human studies that have been published since then.